Shift in Word Formation Process of Indonesian Words - Rusdi Noor Rosa (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
This article is based on the part of the research entitled “Pergeseran Sistem Pembentukan Kata Bahasa Indonesia: Kajian Morfologi dan Sosiolinguistik”. This research is aimed at revealing the shift in Indonesian word formation. The data of this research are Indonesian words formed through word formation. The data were taken from Indonesian newspapers, tabloids, and magazines. The findings show that the shift happened in the processes of Indonesian word formation including borrowing, translation, derivation, acronym, blending, and clipping